PENGARUH KUALITAS PELAYANAN, PROMOSI DAN CITRA MEREK TERHADAP KEPUASAN KONSUMEN E-COMMERCE SHOPEE (Studi Kasus Pada Pengguna E-commerce Shopee di Kecamatan Bogor Timur Kota Bogor) - Anisa Nur Aini; Rachmat Gunawan; Ismartaya (Jurnal Cakrawala Ilmiah, 2024)
In this increasingly growing era of globalization, the sophistication of information technology, including the internet, has had a major impact on all aspects, including the development of the world of business and marketing. This research aims to analyze the influence of service quality, promotion and brand image on Shopee e-commerce consumer satisfaction (case study of Shopee e-commerce users in East Bogor District, Bogor City). The sample of this research was 100 respondents using a non-probability sampling technique or approach using a purposive sampling method. The form of this research is descriptive and verification using multiple linear regression analysis methods. The results of this research show that simultaneously and partially the variables of service quality, promotion and brand image have a positive and significant effect on Shopee e-commerce consumer satisfaction among Shopee e-commerce users in East Bogor District, Bogor City.